Small-scale field evaluation of the efficacy and residual effect of Fludora® Fusion (mixture of clothianidin and deltamethrin) against susceptible and resistant Anopheles gambiae populations from Benin, West Africa - Fiacre R. Agossa; Gil G. Padonou; Arsene Jacques Y. H. Fassinou; Esdras M. Odjo; Osei K. Akuoko; Albert Salako; Zinsou C. Koukpo; Udoka C. Nwangwu; Bruno Akinro; Michel Sezonlin; Martin C. Akogbeto (Malaria Journal, 2018)
Abstract Background In recognition of the threat of insecticide resistance in vectors of malaria, the WHO Global Malaria Programme recommends the development of an appropriate and comprehensive response to insecticide resistance. In principle, good resistance management practice requires the application of multiple insecticides of different modes of action, for example, in rotations and mixtures. Insecticides recommended by the World Health Organization for indoor residual spraying and long-lasting insecticide nets are limited. It is, therefore, judicious to prevent the rapid spread of insecticide resistance by evaluating new insecticides formulations with different modes of action and long residual effect. Methods Fludora® Fusion, a new neonicotinoid IRS formulation (a mixture of 500 g/kg clothianidin and 62.5 g/kg deltamethrin applied 200 mg ai/sqm + 25 mg ai/sqm, respectively) was tested. Small scale field evaluation of this product was conducted in the district of Dangbo in Benin, to compare its efficacy and residual effect on cement and mud walls against those of clothianidin 200 mg ai/sqm (WG 70) alone, and of deltamethrin 25 mg ai/sqm (WG 250) alone. WHO wall cone bioassays were conducted monthly with laboratory susceptible Anopheles “Kisumu” and wild Anopheles gambiae sensu stricto (s.s.) population from Dangbo. The induced mortality by each treatment per wall substrate for 24 h, 48 h, and 72 h post exposure were recorded every month and analysed. Results Fludora® Fusion and clothianidin WG 70 showed mortality rates over 80% WHO bio-efficacy threshold on cement walls either with susceptible or resistant An. gambiae s.s. over a period of 10 and 9 months, respectively. Treatment with Fludora® Fusion and clothianidin WG 70 on the mud walls showed residual effect for 6 months and 5 months respectively against both susceptible and resistant mosquitoes. During the whole evaluation period, deltamethrin WG 250 showed mortality rates below 80% against resistant Anopheles population. Furthermore, the knock down ...